Etnografi Komunikasi Digital: Testimoni Konsumen Men’s Underwear Di Marketplace Tokopedia Dan Shopee - Toni, Ahmad; Maknunah, Jauharotul (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
The research is an analysis of the behavior of a number of marketplaces that are in great demand by Indonesia people, namely Tokopedia and Shopee in reviewing products they have purchased. The research method used in this research is digital ethnography which tries to reveal the motives and meaning as well as the world view of the marketplace consciously by consumers of Tokopedia and Shopee underwear. The primary data in this research is consumer review conversation data, screenshots, and interviews with reviewers in the second marketplaces. The secondary data in this research is various literature related to consumer behavior. The results of the research show that exhibitionist sexual behavior dominates reviews with vulgar photos and videos showing male genitals, buttocks and other sexy body parts. This proves that there are no ethical controls carried out by the three marketplaces in order to protect other consumers.